A novel stochastic modelling approach for electric vehicle charging power and energy requirements - Fazeli, Amir; Johnson, Christopher Mark; Sumner, M.; Christopher, Edward (2015)
Electrification of heat and transport in addition to integration of intermittent renewable resources into the existing electricity network is expected to occur in near future. Such a transformation is expected to force the operation of the electricity power system at different levels to its limits. A novel bottom up modelling approach for quantifying temporal variation of electric vehicle charging power and energy is presented in this paper which can be used to accurately investigate the effect of charging different penetration levels of electric vehicles within the low voltage distribution network. This EV charging model is further used for development of a deterministic control algorithm for regulating power flows at the low voltage level.